2018
DOI: 10.1186/s13014-018-1161-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone density and pain response following intensity-modulated radiotherapy versus three-dimensional conformal radiotherapy for vertebral metastases - secondary results of a randomized trial

Abstract: BackgroundThis was a prespecified secondary analysis of a randomized trial that analyzed bone density and pain response following fractionated intensity-modulated radiotherapy (IMRT) versus three-dimensional conformal radiotherapy (3DCRT) for palliative management of spinal metastases.Methods/materialsSixty patients were enrolled in the single-institutional randomized exploratory trial, randomly assigned to receive IMRT or 3DCRT (30 Gy in 10 fractions). Along with pain response (measured by the Visual Analog S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…These studies uniformly showed an increase in density after radiation. Also, with the exception of one study in which osteolytic and osteoblastic lesions were markedly underrepresented [8], these studies indicated that increased density following radiation trended toward or was significantly greater in magnitude as the lytic component of lesions increased across different histologies and lesion sites. Bone pain, opioid consumption, and quality of life have all been demonstrated to be inversely correlated with bone density.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…These studies uniformly showed an increase in density after radiation. Also, with the exception of one study in which osteolytic and osteoblastic lesions were markedly underrepresented [8], these studies indicated that increased density following radiation trended toward or was significantly greater in magnitude as the lytic component of lesions increased across different histologies and lesion sites. Bone pain, opioid consumption, and quality of life have all been demonstrated to be inversely correlated with bone density.…”
Section: Discussionmentioning
confidence: 90%
“…There has been some suggestion that even bone outside of the radiation field may have its density impacted due to effects on bone marrow stem cells [24]. However, this has not been a consistent finding [8,10,17,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid pain relief (even after 24 h), observed in some patients, indicates a decrease of inflammatory cell activity as well as chemical pain mediators concentration in the radiation field, which play a role in the analgesic effect of radiation [15]. The RT fractionation scheme in patients with bone metastasis influences the level of mineralization, bone density, and recalcification of the irradiated site [16,17], which is associated with pain response. The recalcification rate was lower in the single fraction group (120%) compared to patients who received fractionated RT (173%, p < 0.0001) with a slight trend favouring 10 × 3 Gy RT scheme [17].…”
Section: Painful Bone Metastasesmentioning
confidence: 99%